Purification and characterization of the plastid‐localized NAD‐dependent malate dehydrogenase from Arabidopsis thaliana. (28th August 2015) - An, Yan; Cao, Youzhi; Xu, Yingwu
Abstract: Malate dehydrogenase (MDH) ubiquitously exists in living organisms and has many isoforms in a single species. MDHs from some classes have been characterized for their catalytic properties, which show significant variations despite that they share high sequence identity for the active sites. One class MDH, the plastid‐localized NAD‐dependent MDH (plNAD‐MDH) is known to be important for plant survival in a dark environment, but its biochemical and enzymatic properties have not been well characterized. This study attempts to fill the gap. plNAD‐MDH was expressed in an Escherichia coli system and purified using nickel‐affinity chromatography followed by size exclusion chromatography. The N‐terminal fusion his‐tag was removed by protease cleavage. The gel filtration assay and glutaraldehyde cross‐linking results showed that the active enzyme was a homodimer in solution. Further assay indicated that plNAD‐MDH is most active at a neutral pH value. The K m values for oxaloacetate and NADH are found in the submillimolar order, a median range for most MDHs. The maximum reaction rate values, however, are dramatically different from other plant MDHs, indicating that plNAD‐MDH has different substrate specificity. Moreover, we obtained crystals for this enzyme, which laid the groundwork for further analysis of the enzymatic mechanism from structural stand point.